(untitled) (Research, Society and Development, 2022)
It’s believed that the hospital concierge can bring increment and provide an improvement in the services provided. As part of the user experience during hospitalization in a hospital, the service and the environment offered play an important role, since they can impact the process of restoring the patient’s health. Therefore, attention to the user’s perception of the service provided, as well as the identification of improvements in the service offered based on these perceptions, is necessary. The present study aims to evaluate patients’ perception of physical evidence and intangible elements of the service environment in their experience with the delivery of hospital concierge services, in order to point out improvements in the inpatient unit evaluated. For this, a framework was developed that integrates the service blueprint approach of experience with the approach of the servicescape in physical evidence, from which a questionnaire was structured applied to 100 patients and/or caregivers (service users) to assess the perception of patients. patients in a clinical surgical inpatient unit. The results indicate for which attributes evaluated (tangible and intangible) the users attributed the highest average score, indicating greater importance in the perception of the evaluation of the quality of the service provided and, on the other hand, for which attributes were attributed the lowest average scores, requiring in the latter some changes to improve the perception of service users.